2018
DOI: 10.24043/isj.50
|View full text |Cite
|
Sign up to set email alerts
|

“The place where I live is where I belong”: community perspectives on climate change and climate-related migration in the Pacific island nation of Vanuatu

Abstract: ABSTRACT:In recent years, narratives of the 'climate refugee' have abounded within the larger conversation regarding climate change. However, anthropologies from climatevulnerable Pacific Islands-particularly those most targeted by 'climate refugee' discoursehave determined that the way many media outlets and policy specialists speak of climaterelated migration is sensationalized, over-simplistic, and unrepresentative of how Pacific Islanders approach the issue. Aimed at illustrating how local context can add … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…The papers in this special thematic section examine a wide geographical range of islands (see Figure 1), with three in the South Pacific (Beyerl et al, 2018;Perkins & Krause, 2018;Perumal 2018), one in the Caribbean (Robinson, 2018), and one in the British Isles (Petzold, 2018). Two papers discuss islands groups which are extraterritorial lands and which are not SIDS (Ferdinand, 2018;Schwebel, 2018), and one takes a theoretical approach (Kelman, 2018).…”
Section: Content Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers in this special thematic section examine a wide geographical range of islands (see Figure 1), with three in the South Pacific (Beyerl et al, 2018;Perkins & Krause, 2018;Perumal 2018), one in the Caribbean (Robinson, 2018), and one in the British Isles (Petzold, 2018). Two papers discuss islands groups which are extraterritorial lands and which are not SIDS (Ferdinand, 2018;Schwebel, 2018), and one takes a theoretical approach (Kelman, 2018).…”
Section: Content Reviewmentioning
confidence: 99%
“…Also from the South Pacific, Perumal (2018) draws from data collection in Vanuatu to challenge some of the reductionist narratives of climate change related migration and the often sensationalist use of the label 'refugee'. Specifically examining the perspective of ni-Vanuatu policymakers and climate activists, this research uncovers a reluctance to relocate at all due to climate change: Moving is truly a last resort, and the preference is for in situ adaptation and maintenance of cultural and livelihood continuity.…”
Section: Content Reviewmentioning
confidence: 99%
“…In particular, the "refugees" and "forced migration" trope highlights the supposed situation of movement being involuntary and leaving one's country of origin directly because of impacts from climate change. This assumption contrasts with the interviewees expecting and presuming that they choose how and when they migrate and that they will have destination choices, including remaining within their country-similar to the findings in Vanuatu (Peruma 2018).…”
Section: Discussionmentioning
confidence: 77%
“…Mortreux and Barnett (2009) found in Funafuti (Tuvalu) that respondents hardly cite climate as reason to migrate, and they criticise outsiders' view of migration as adaptation because it involves much cultural loss. Similarly, research from Vanuatu reveals a strong reluctance to resettle and a prioritisation of in situ adaptation measures (Perumal 2018). In a study of Kiribati, Allgood and McNamara (2017) found that climate-induced migration and displacement was already common.…”
Section: Introductionmentioning
confidence: 99%